2018
DOI: 10.1038/s41419-017-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a-5p attenuates irradiation-induced and LPS-induced hepatic stellate cell activation and hepatocyte apoptosis through inhibition of TLR4 pathway

Abstract: Elevated toll-like receptor 4 (TLR4) expression is associated with a high risk of radiation-induced liver disease (RILD). MicroRNA (miR)-146a-5p is a key regulator of lipopolysaccharide (LPS)/TLR4 signaling, but its role in modulation of RILD remains unclear. Here, we found that irradiation and LPS stimulation induced TLR4 and miR-146a-5p expression in the human hepatic stellate cell (HSC) line LX2. Ectopic expression of miR-146a-5p in LX2 inhibited irradiation-induced and LPS-induced pro-inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…In this study, we inflammatory responses and fibrogenesis in the process of liver injury (Fujita & Narumiya, 2016;Gandhi, 2017). Our previous study also confirmed that HSCs serve as effector cells during the development of RILD (Chen et al, 2018). RAC1 has been demonstrated to be involved in the process of liver injury.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, we inflammatory responses and fibrogenesis in the process of liver injury (Fujita & Narumiya, 2016;Gandhi, 2017). Our previous study also confirmed that HSCs serve as effector cells during the development of RILD (Chen et al, 2018). RAC1 has been demonstrated to be involved in the process of liver injury.…”
Section: Discussionsupporting
confidence: 74%
“…Li et al showed that inhibiting the expression of TLR4 in cartilage lessened the severity of OA in the rat model (34). miRNAs have been found to affect the activation of TLR4 (35-38). For example, Chen et al found that miR-20a negatively regulated TLR4 signaling under atherosclerotic risk (39).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory inducer LPS has been shown to induce autophagy in the liver hepatocytes and HSCs [32][33][34] . We firstly established in vitro trials on HSC-T6 cells by LPS stimulus.…”
Section: G-rg3 Exerted Anti-fibrotic Effect Through Inhibiting Lpsindmentioning
confidence: 99%